Academic reading attitudes of undergraduate english language learners - Melati; Safitri , Nyimas Triyana; Mardiah , Radiatan (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
In academic setting, reading is an important activity as this activity provides students with useful information for the students to produce scholarly outcomes. There are reading resources available online and printed so the students can choose which version that are convenient to them, both with their respective benefits and weaknesses. However, research shown that students have low motivation to approach their reading assignment for their college studies. Thus, this research is conducted in order to figure out the academic reading attitude of students in one university in Indonesia as it will provide information about recent attitude toward academic reading. In collecting data, this research uses Isakson Survey of Academic Reading Attitude (ISARA). The results indicate that students have moderate level of academic reading attitude in three areas, namely value, self-efficacy, and behavior components. By recognizing this attitude, students can gain more motivation to accomplish their academic reading and be more aware of the importance of the relation between having positive reading attitude and their reading achievement afterwards.